![image](https://tex.z-dn.net/?f=%28x-2%29%5E%7Bx%5E2-6x%2B8%7D%3E1)
1" alt="(x-2)^{x^2-6x+8}>1" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=%28x-2%29%5E%7Bx%5E2-6x%2B8%7D%3E%28x-2%29%5E0)
(x-2)^0" alt="(x-2)^{x^2-6x+8}>(x-2)^0" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=%28x-4%29%28x-2%29%3E0)
0" alt="(x-4)(x-2)>0" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=x_1%3E4)
4" alt="x_1>4" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=x_2%3E2)
2" alt="x_2>2" align="absmiddle" class="latex-formula">